Tax amnesty dan Implementasinya - I Nyoman Putra Yasa; I Putu Wahyu Mandala (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2016)
The purpose of this research is to examine the implementation of tax amnesty in Indonesia. Taxamnesty is an old policy that try again offered by the Government of Indonesia after 1964 and 1984,never failed to increase the acceptance of the State. In pengimplementasiannya one of the weakness of the Tax amnesty when applied in Indonesia is can lead to a variety of abuses and a moral hazard because the facilities and infrastructure, information access and openness to the other supporters have not been adequate as a prerequisite the enactment of a tax amnesty. With the new law that is the regulatory umbrella of the Directorate General of Tax number 11/PJ/2016 about Further Arrangements regarding the implementation of law number 11 Year 2016 on the remission of tax (a Tax amnesty). The new rule was created in order for thecommunity to have the principle of Justice for the community. This rule can clarify the previous rule diharpakan which rated troubling society. The application of a tax amnesty to some of the things of which implicates 1) an increase in the taxpayer-driven policies tax amnesty .2) an increase in the receipt of State revenue, caused an increase in the Taxpayers because of the policy of tax amnesty, 3) related to national development,adaningkatan ya pepenerimaan pandapatan State because the tax will make the construction morerunning smoothly and diharapan can simplify and enhance the well-being of society